Strategi Manajerial Kepala Sekolah Dalam Penguatan Pendidikan Karakter Siswa Pada Lingkup Atensi Moderasi Beragama di SMA NEGERI 1 LIMA PULUH - Azizi, Ahmad Raihan; Chaniago, Nasrul Syakur; Akhyar, Sayed (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study, titled "The Principal's Managerial Strategies in Strengthening Students' Character Education within the Context of Religious Moderation at SMA Negeri 1 Lima Puluh," is motivated by the strong sense of tolerance and harmony among different religious communities within the school environment, despite the limited support for the character education program. The study aims to describe the principal's strategies in planning, implementing, organizing, supervising, and evaluating character education with a focus on religious moderation. A qualitative approach with a descriptive method was employed, involving the principal, vice principals, and teachers as the main sources of information. The findings reveal that the planning strategy at SMA Negeri 1 Lima Puluh includes a vision, mission, character education focused on religious moderation, and collaboration between the principal and teachers. The organizational strategy applies a systematic approach involving annual planning to create an inclusive environment and ensure the program's relevance. Implementation is carried out in a structured and integrative manner, without specific strategies, yet remains aligned with the school’s vision and mission. Supervision and evaluation are conducted through regular meetings, scheduled evaluations, and disciplinary reporting, ensuring the effectiveness and sustainability of the character education program. This approach reflects a commitment to strengthening students' character holistically and sustainably, consistent with relevant managerial theories.